Exploratory review on understanding the relationship between cultural services and open space in university - Harun, Nor Zalina; Ibrahim, Putri Haryati; Rosli, Nur Diana Shafikha (American Scientific Publishers, 2017)
Open space in University offers multiple ecosystem services, providing a variety of benefits to human life. Ecosystem services are defined as the advantages that people receive from the ecosystems. It is the conditions and processes through which natural ecosystems and the species are to sustain and fulfill human life. In current research stated, the ecosystem contribute to human well-being has been emphasized with less attention to the important of cultural services as there is a significant changes in people interaction with environmental settings. Cultural services are recognized, but it is not yet defined clearly within the ecosystem services framework how important it is to human wellbeing. Thus, this paper is aim to explore the understanding of the relationship of cultural services and open space in University. Hence, the objectives of this research are to study the cultural services functions and to identify the values of cultural services provided. It is to understand how knowledge of cultural services related to the socio-cultural value of human wellbeing. The research methods used consisted of a document analysis of cultural services with socio-cultural value through open space in University. The finding of this study is to demonstrate the proposed framework which shows the link between cultural services and socio-cultural value to human wellbeing. Above all, this approach is to understand the comprehensive approach to demonstrate the important of cultural services and open space within the campus to human wellbeing.